Morphological characters of the seed coat in selected species of the genus Hypericum L. and their taxonomic value - Szkudlarz, Piotr; Celka, Zbigniew (Biodiversity: Research and Conservation, 2016)
Eight Hypericum species are native to Poland: H. elegans Stephan ex Willd., H. hirsutum L., H. humifusum L., H. maculatum Crantz, H. montanum L., H. perforatum L., H. pulchrum L., and H. tetrapterum Fr. Only seeds of H. elegans were investigated in detail in Poland before, so here we present results of qualitative and quantitative analyses of seed morphology of the other 7 species, based on characters like seed length, width, and shape, seed coat sculpture, shape of epidermal cells of the testa, and number of epidermal cells along the seed axis. The results show that seeds of the studied species are small, 0.56-1.15 mm long and 0.26-0.49 mm wide. In SEM images, seed coat sculpture is reticulate in 5 species, papillate in H. hirsutum, and cup-shaped in H. pulchrum. The differences are caused by the varied final development of the testa epidermis, which constitutes the outer layer of the seed coat. The mean number of epidermal cells along the seed axis ranges from 22 to 33. Results of cluster analysis, based on the agglomeration method and including also published data on seeds of H. elegans, show that the variation in the investigated characters of seeds is reflected in the taxonomic division of the genus into sections.